2020
DOI: 10.1055/a-1244-1621
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Body Mass Index on Softball Pitchers’ Hip and Shoulder Range of Motion

Abstract: Currently it is hypothesized that increased body mass index may contribute to overuse injuries. Thus, if hip or shoulder range of motion is affected by body mass index, pitchers may be placing additional stress on joints as they seek to pitch at maximal velocity. The purpose of this study was to examine if range of motion at the hips and shoulders were related to body mass index classification. A sample of 147 female softball pitchers (17.0±4.2 years; 167.6±11.8 cm; 70.6±17.5 kg; body mass index=24.8±4.7 kg/m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Those who possess extra fat mass might be less active and, as a result, perform fewer and less intense repetitions. Interestingly, a previous report also found that pitchers with higher body mass index did not achieve as much dominant shoulder ER ROM as those with lower body mass index (Friesen et al, 2020a ). Therefore, adaptation maybe does not occur the same in a population of pitchers with increased mass and body fat.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Those who possess extra fat mass might be less active and, as a result, perform fewer and less intense repetitions. Interestingly, a previous report also found that pitchers with higher body mass index did not achieve as much dominant shoulder ER ROM as those with lower body mass index (Friesen et al, 2020a ). Therefore, adaptation maybe does not occur the same in a population of pitchers with increased mass and body fat.…”
Section: Discussionmentioning
confidence: 88%
“…Originally, it was hypothesized that the high fat% group might display decreased ROM in general, due to the impingement issues that arise from exhibiting increased fatty tissue. Research points out that those pitchers with a higher body mass index possess less bilateral hip ROM, hypothesized to be the result of greater impinging tissue (Friesen et al, 2020a ). It was also expected that the greater mass associated with those in the high bf% group might accrue greater adaptation due to increased loading on the joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Second, only the acceleration phase of the pitch was analyzed. Previous research noted that elbow flexion is greatest during the initial upswing of the pitching arm in preparation for the acceleration phase and during followthrough, 10 while the largest shoulder distraction forces occur during the acceleration phase of the pitch. 4,28 Elbow flexion occurring early in the pitching cycle may have more influence on acceleration phase kinetics and may help to predict later kinematics such as that during ball release and the acceleration phase.…”
Section: Discussionmentioning
confidence: 97%
“…Research shows the higher rate of injury associated with increased body mass [8]; therefore, it is important to understand potential biomechanics influenced by body fat and mass in striving to understand the mechanism of injury. Research shows there are altered kinematics present among those pitchers with increased body fat [28] and altered ranges of motion available for those with higher BMI [16]. Perhaps kinematics and body functional characteristics are most altered by varying levels of pitcher body fat and contribute to various pitch outcomes more so than force-generating characteristics.…”
Section: Discussionmentioning
confidence: 99%